Description of three new species of Helconichia Sharkey & Wharton (Hymenoptera: Braconidae: Ichneutinae) with a revised key to all species - Sharanowski, Barbara J.; Sharkey, Michael J. (Zootaxa, 2007)
Three new species of Helconichia Sharkey & Wharton are described: H. sarria Sharanowski and Sharkey, sp. nov. and H. reina Sharanowski and Sharkey, sp. nov. from Colombia, and H. brenesi Sharanowski and Sharkey, sp. nov. from Costa Rica. These species double the number of described species of Helconichia, bringing the total number to six. The key of Sharkey and Wharton (1994) is revised to include the new species. Lateral habitus images of all six holotypes of the species of Helconichia are included, in addition to images of character states used in the identification key.